Teachers’ Perception of Differentiated Instruction for Slow Learner in Inclusive School Yogyakarta - Rosi, Fahrur; Zen, Evynurul Laily; Nurjannah, Siti (Universitas Cokroaminoto Palopo, 2024)
This present study aims to find out the teachers’ perception and practice about the implementation of Differentiated Instruction (DI) in English-as-a-foreign-language (EFL) teaching to students with Slow Learner (SL) in inclusive school. This study employed a descriptive qualitative method conducted at Junior high school in Yogyakarta, Indonesia, by selecting two English teachers as participants. The data were collected through observation, interview and document. The findings revealed that the teachers do not fully comprehend the concept of DI, especially in the analysis of student learning profiles, even though socialization regarding differentiated learning has already been given by the government. The challenges that teachers encountered were the insufficient training on how to identify and accommodate the needs of slow learner students, who constitute a large proportion of their classes. In concussion, the English teachers have already had the basic concept of differentiated learning, but have not been able to implement it effectively in practice.